The Atlas of Emergency Medicine - Knoop, Kevin J.; Stack, Lawrence B; Storrow, Alan B; Thurman, R. Jason (Robert Jason) (McGraw-Hill Education, 2021)
With fully updated treatment information, guidelines, and diagnostic testing, The Atlas of Emergency Medicine is the go-to visual guide for treating and diagnosing problems for both typical and atypical conditions. You'll find invaluable information for virtually any medical issue you're likely to encounter. Every topic includes at least one color photo showing what you need to look for, along with text descriptions written concisely and right to the point. The book is organized by organ system, special populations, and general issues enabling you to secure the facts and data you need on the spot.